Evaluation of left renal vein entrapment using multidetector computed tomography - Poyraz, Ahmet K.; Firdolas, Fatih; Onur, Mehmet R.; Kocakoc, Ercan (Royal Soc Medicine Press Ltd, 2013)
Background: Nutcracker syndrome, also called left renal vein entrapment syndrome, is a cause of non-glomerular hematuria with difficulties in diagnosis. Multidetector computed tomography (MDCT) is a powerful tool to prevent unnecessary diagnostic procedures. Purpose: To retrospectively determine the prevalence of nutcracker phenomenon and nutcracker syndrome seen in MDCT in consecutive patients. Material and Methods: The institutional review board approved the study and waived the requirement for informed consent. Abdominal contrast-enhanced MDCT scans were reviewed from 1000 consecutive patients. MDCT scan assessment included renal vein diameter measurements and evaluation for the presence of anterior or posterior left renal vein entrapment. Electronic medical records and urine analysis reports of patients with left renal vein entrapment were reviewed. Student's t test was used to assess differences in renal vein diameter in patients with left renal vein entrapment. Results: Left renal vein entrapment was observed in 10.9% (109), retro-aortic left renal vein in 6.5% (65), entrapment of left renal vein between superior mesenteric artery and aorta in 4.1% (41), and circumaortic left renal vein in 0.3% (3) of patients. Mean diameters of right (8.8 +/- 1.9 mm) and unentrapped left (8.9 +/- 1.8 mm) renal veins were not significantly different (P = 0.1). The mean diameter of anterior entrapped left renal veins (10.3 +/- 2 mm) was significantly greater (P = 0.04) than contralateral renal veins (8.6 +/- 2.1 mm) in their widest portion. In 8.8% of patients with the left renal vein entrapment, urine analysis showed isomorphic hematuria or proteinuria with no other known cause. Varicocele and pelvic congestion were seen in 5.5% of patients with the left renal vein entrapment. Conclusion: Left renal vein entrapment is not a rare entity and renal nutcracker phenomenon might be underdiagnosed.
Keywords: Left renal vein entrapment; nutcracker syndrome; computed tomography